Eco-Friendly Synthesis of Magnesium Oxide Nanoparticles Using Eggplant (Solanum melongena) Extract: Structural and Morphological Characterization: Sintesis Ramah Lingkungan Partikel Nano Oksida Magnesium Menggunakan Ekstrak Terong (Solanum melongena): Karakterisasi Struktur dan Morfologi - Hiyam Raheem Sharhan (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Nanotechnology enables the design of advanced materials with unique physicochemical properties at the nanoscale. Specific Background: Magnesium oxide nanoparticles are widely studied due to their high stability, biocompatibility, and applicability in catalysis, environmental remediation, and antimicrobial systems. Knowledge Gap: Conventional synthesis methods often involve toxic chemicals and complex processing, while systematic studies using eggplant extract remain limited. Aims: This study aims to synthesize MgO nanoparticles using aqueous eggplant extract as a bio-reducing and stabilizing agent and to evaluate their structural and morphological properties. Results: XRD confirmed phase-pure cubic MgO with a rock salt structure and an average crystallite size of 18.56 nm. FESEM analysis showed quasi-spherical morphology with an average particle size of 23.14 nm, while EDX verified stoichiometric Mg and O composition with high purity. FTIR identified characteristic Mg–O vibrations and residual phytochemical functional groups. Novelty: The study demonstrates the use of eggplant extract as a sustainable bio-resource for producing well-crystallized MgO nanoparticles. Implications: The synthesized nanoparticles exhibit nanoscale dimensions and structural purity suitable for applications in catalysis, environmental remediation, and antimicrobial systems. Keywords: Magnesium Oxide Nanoparticles, Green Synthesis, Eggplant Extract, Structural Characterization, Nanomaterials Key Findings Highlights Phase-pure cubic structure verified through diffraction analysis Biogenic synthesis produced uniform nanoscale morphology Elemental composition confirms high chemical purity